Tokoh Punakawan Pada Wayang Orang Sebagai Sumber Ide Penciptaan Animasi 2d Dengan Konsep E-Learning - Rachman, Anung (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2009)
The problem in the rising generation society concerning local culture are conflicting between the needs of rising generation society to have a suistainable edutainment as unity of a â€œliving cultureâ€, with many changes affected from the importing culture developed by foreign resources, high technology and the pressure by the world culture growth. Panakawan as one of culture local figure variety have many utilized by art agents as inspiration of art creating and creation media with various artistry shaped. It oftentimes we can see, considering on pana-awan's figure there are many contain positive simbol that is utilized to build nation personality. But unhappily current, the local culture is getting not popular among the rising generation because itâ€™s ingoing the import culture to this nation with in fast. By the encapsulate local tradition and animation (modern technology) method for the research we have destination that the rising generation society can feel comfort and back to local culture as nation wealth. With animations technology, an object at computer can be made more interesting because this technology make the object moving and becomes â€˜ lifeâ€™. The encapsulation is made with e-learning method. The result is edutainment creation. The user which exploit it will be given local culture education and entertainment all at once. e-learning is define as learning method with technology (electronic) supporting.Â Keywords:Â local culture, animasi, e-learning